Road hazards and human resources productivity in Nigeria / A. Salman, S. B. Isiaka and M.J. Saka - Salman, A.; Isiaka, S. B.; Saka, M.J (Universiti Teknologi MARA, Perlis, 2017)
Transport is a major key factor in modern economies. In fact, cities and transport have developed hand-inhand since the earliest large human settlements. Problems such as road congestions and other forms of road hazards hinder the objective of human resource productivity and transportation systems. This paper however, examined the impact of roads hazards on human resources productivity in Nigeria. The respondents were made up of drivers, passengers, pedestrians, security officers, market women and men, and farmers. Thirty-five (35) respondents were selected at strategic areas through stratified and simple random sampling techniques from each selected areas of the states under study. Z-score statistical tool was adopted. It was concluded that road hazards has negative effects on the productivity of human resources in Nigeria. The study, therefore, recommended that road hazards can be drastically reduced by embarking on various prevention and implementation of strategies such as: implement mobility management, improving traffic operations, etc.